Evaluation of single intra-dermal test and commercial ELISA for diagnosis of paratuberculosis in Indian cattle population - TRANGADIA, B J; DEC BRONSVOORT, B M; HANDEL, I G; NAGMANI, K; RANA, S K; CHANDRAN, DEV; SRINIVASAN, V A (The Indian Journal of Animal Sciences, 2014)
Between May 2008 and March 2009, serum samples (1,170) were collected from indigenous purebred and crossbred cattle housed in 15 organized farms located across seven states of India. These sera were tested for the presence of antibodies against Mycobacterium avium paratuberculosis (Map). After blood collection, all these animals were screened for paratuberculosis by single intra-dermal injection of Johnin protein purified derivatives. The Hui-Walter, no gold standard approach under the assumption of conditional independence was used to estimate sensitivity and specificity of these 2 tests and the prevalence of paratuberculosis in these populations. The estimated sensitivities were 18.2 and 26.6% for SIT and ELISA, respectively, whereas, specificities were 98.0 and 92.4% for SIT and ELISA, respectively. The results indicated that both tests were very insensitive but, the SIT was reasonably specific. The sero-prevalence estimates of Map varied from 7.0% in Uttar Pradesh to 77.9% in Tamil Nadu. As it is difficult to estimate the full impact of either of these tests for use in control or surveillance of this disease, there is a need to develop improved tests for field use in India.